2004
DOI: 10.1359/jbmr.0301242
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Glucocorticoid-Induced Apoptosis in Osteocytes and Osteoblasts by Calbindin-D28k

Abstract: This study show for the first time that calbindin-D 28k can prevent glucocorticoid-induced bone cell death. The anti-apoptotic effect of calbindin-D 28k involves inhibition of glucocorticoid induced caspase 3 activation as well as ERK activation.Introduction: Recent studies have indicated that deleterious effects of glucocorticoids on bone involve increased apoptosis of osteocytes and osteoblasts. Because the calcium-binding protein calbindin-D 28k has been reported to be anti-apoptotic in different cell types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(79 citation statements)
references
References 64 publications
(90 reference statements)
6
72
0
1
Order By: Relevance
“…25 Other studies have addressed the effects of Dex on osteogenic cell lines or on primary isolates of osteogenic cells, and often used high Dex concentrations (10 À6 M). 26 One other study showed a nearly linear relationship between rate of apoptosis induction and Dex concentration in a range from 10 À6 to 10 À9 M in murine osteogenic cells, 27 but these cells are farther along the osteogenic lineage than are MSCs. In the present study, higher levels of apoptosis were observed in cultured human bone marrow MSCs at confluence in standard medium, but apoptosis was reduced in Dex supplemented medium.…”
mentioning
confidence: 99%
“…25 Other studies have addressed the effects of Dex on osteogenic cell lines or on primary isolates of osteogenic cells, and often used high Dex concentrations (10 À6 M). 26 One other study showed a nearly linear relationship between rate of apoptosis induction and Dex concentration in a range from 10 À6 to 10 À9 M in murine osteogenic cells, 27 but these cells are farther along the osteogenic lineage than are MSCs. In the present study, higher levels of apoptosis were observed in cultured human bone marrow MSCs at confluence in standard medium, but apoptosis was reduced in Dex supplemented medium.…”
mentioning
confidence: 99%
“…For the analysis of gene expression, SaM-1 cells were cultured in 6 cm dishes at a density of 1.5ϫ10 5 cells/dish (proliferative stage) for the indicated periods, and then the total RNA was extracted using QIAzol Lysis reagent. The other cell lines were cultured in 10-cm dishes at a density of 1ϫ10 5 cells/dish (proliferative stage) for the indicated periods, and then the total RNA was extracted.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6] In addition to their direct effects on osteoblasts, they have also been demonstrated to modify the synthesis of growth factors produced by osteoblastic cells. [7][8][9] These effects lead to the suppression of bone formation, a central feature in the pathogenesis of glucocorticoid induced osteoporosis.…”
mentioning
confidence: 99%
“…[31][32][33] The decrease in osteoblast differentiation includes induction of adipogenetic transcription factors (PPARγ) and suppression of Wnt protein signalling; [34][35][36][37] the increase of osteoblast and osteocyte apoptosis is associated with caspase 3 activation. 38 Moreover, the osteoblast function is decreased through the antianabolic effects of GCs, such as decrease in GH, IGF1 and IGFBP 3-4-5 . In contrast, GCs increase IGFBP 6 transcription thus decreasing IGF2, another local regulator of osteoblast function.…”
Section: Bone Effects Of Gcsmentioning
confidence: 99%